Sustainable software development : an agile perspective - Tate, Kevin (Agile software development series., 2005)
"Over the years I have seen the software development pendulum swing from one extreme to the other, as deficiencies in 'best practices' at one end of the spectrum spawned a new set of 'best practices' at the opposite end. Kevin Tate's book has finally brought the pendulum to a screeching halt, right about dead center. This book provides a balanced and practical guide to what's important if your goal is to develop software that lasts." -Mary Poppendieck, Poppendieck.LLC. Author of "Lean Software Development" "1) In this very practical and accessible book interspersed with real-world examples and personal opinions, Kevin has distilled his years of developing quality software into a set of principles and practices that have been proven to work. If you are thinking of introducing an agile development environment (ADE) into your organization or of improving the one you already have, this book will help you clearly understand the benefits of a sustainable ADE, establish the practices to make it happen and coach you through the follow-up required to change the culture of your organization to make sure the changes take hold. I am currently faced with exactly this challenge and this book has already given me several ideas I am looking forward to trying out. 2) In an industry plagued with missed deadlines despite long overtime hours, this book offers a refreshing alternative: a set of guiding principles and simple practices to follow that allow you to get the job done by working smarter, not harder. Drawing on the author's extensive experience developing quality software, the book clearly explains the principles behind a sustainable agile development environment, why it works, the practices to make it happen and the follow through required to turn these practices into habits." -Peter Schoeler, Technical Director, Artificial Mind & Movement "It's a familiar scene-the schedule's tight, people are putting in heroic efforts to get everything done, then at the last minute a change request comes in that wipes out the gains you had finally managed to make in meeting your ship date. Looks like it's pizza at your desk for the weekend again! An unfortunate situation to be in but a pattern that repeats itself all too often. "Sustainable Software Development" offers hope to break this cycle. It shows how a change in mindset can free you from the tyranny of unrealistic expectations and brings development realities out onto the table for everyone to see. By following ...